Integration of Unemployed Venezuelan Immigrant Women in Colombia (2024)
The integration of immigrants in a host society must consider aspects related to the labour field, as well as other factors including their differences. The existence of 97 unemployed Venezuelan migrant women living in Cúcuta, Los Patios and La Parada, border cities of Norte de Santander, Colombia with the state of Táchira, places them at a disadvantage in terms of integration; hence, this study set out to propose strategies to guide governance officials and actors in managing their integration. By means of a multidimensional analysis, three profiles of these unemployed migrant women were obtained for their diversity, generating strategies for each profile in structural, social and cultural contexts; through this, it became evident that the characteristics of those who settle as immigrants can be considered in order to establish integration strategies in line with these characteristics. Thus, the methodology of the study could be useful in other areas of migration for the design of integration strategies that consider the heterogeneity of immigrants to facilitate their contribution to the society and economy of the country that has hosted them.